2012
DOI: 10.1186/1746-4811-8-39
|View full text |Cite
|
Sign up to set email alerts
|

A method to quantify infection and colonization of holm oak (Quercus ilex) roots by Phytophthora cinnamomi

Abstract: Phytophthora cinnamomi Rands. is an important root rot pathogen widely distributed in the north hemisphere, with a large host range. Among others diseases, it is known to be a principal factor in the decline of holm oak and cork oak, the most important tree species in the “dehesa” ecosystem of south-western Spain. Previously, the focus of studies on P. cinnamomi and holm oak have been on molecular tools for identification, functional responses of the host, together with other physiological and morphological ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
(45 reference statements)
1
16
0
1
Order By: Relevance
“…On the other hand, proline may act as osmolyte mitigating water stress and balancing turgor pressure during abiotic stress and pathogen invasion at a whole-plant level (61,62). Wilting caused by blockage of xylem by the pathogen and reduction of water supply, is a classical symptom of a root disease on infected chestnut plants (63). Finally, proline may act directly on pathogen propagation and spread because of its significant role in osmoregulation of development and release the P. cinnamomi zoospores (64).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, proline may act as osmolyte mitigating water stress and balancing turgor pressure during abiotic stress and pathogen invasion at a whole-plant level (61,62). Wilting caused by blockage of xylem by the pathogen and reduction of water supply, is a classical symptom of a root disease on infected chestnut plants (63). Finally, proline may act directly on pathogen propagation and spread because of its significant role in osmoregulation of development and release the P. cinnamomi zoospores (64).…”
Section: Discussionmentioning
confidence: 99%
“…5). Blockage of the xylem through hyphal obstruction and deposition of material by the plant inhibits water movement from the roots to the shoots, resulting in water stress (Ruiz G omez et al, 2015). Necrosis of infected fine feeder roots exacerbates the problem and can lead to rapid plant death (McConnell and Balci, 2015;Oßwald et al, 2014).…”
Section: Hyphal Growthmentioning
confidence: 99%
“…Pathogen CWDEs are also secreted through vesicle fusion at the hyphal apex, and the consequent hydrolysis of plant cell walls is indicated by changes in wall morphology, cell separation and tissue maceration (Redondo et al, 2015;Ruiz G omez et al, 2015). There is some evidence that these changes are accompanied by de-esterification of plant cell wall pectins during the infection of holm oak (Quercus ilex) by P. cinnamomi (Ruiz G omez et al, 2015); however, the causal relationship between these features and details of the molecular mechanisms underlying plant cell wall degradation await future research.…”
Section: Hyphal Growthmentioning
confidence: 99%
“…Haustoria, i.e. specialized hyphae capable of penetrating the host cell and absorbing nutrients from the host cytoplasm, were not confirmed in secondary roots of Q. ilex infected by P. cinnamomi (Ruiz-Gómez et al 2012). The authors suggested further electronic microscopy studies to better characterize these structures.…”
Section: Introductionmentioning
confidence: 96%
“…Histology of secondary roots of 6-month-old Q. ilex seedlings revealed alterations of the structure of the tissues when trees were inoculated with P. cinnamomi (Ruiz-Gómez et al 2012. Changes in the host included cell wall thickening, an increase in the number and size of intercellular spaces in the central cylinder, accumulation of phenolic compounds in the middle lamella and of pectic substances which sealed pits of the xylem vessels, and the formation of lignitubers (Ruiz Gómez et al 2015).…”
Section: Introductionmentioning
confidence: 99%